A multicenter, randomized, prospective study of 14-day ranitidine bismuth citrate- vs. lansoprazole-based triple therapy for the eradication of Helicobacter pylori in dyspeptic patients - KOCAKAYA, OZAN (TURKISH SOC GASTROENTEROLOGY, 2013)
Background/aims: Proton-pump inhibitor- and ranitidine bismuth citrate-based triple regimens are the two recommended first-line treatments for the eradication of Helicobacter pylori. We aimed to compare the effectiveness and tolerability of these two treatments in a prospective, multi-centric, randomized study. Materials and Methods: Patients with dyspeptic complaints were recruited from 15 study centers. Presence of Helicobacter pylori was investigated by both histology and rapid urease test. The patients were randomized to either ranitidine bismuth citrate 400 mg bid plus amoxicillin 1 g bid plus clarithromycin 500 mg bid (n=149) or lansoprazole 30 mg bid plus amoxicillin 1 g bid plus clarithromycin 500 mg bid (n=130) treatment arm for 14 days. Adverse events have been recorded during the treatment phase. A C-13 urea breath test was performed 6 weeks after termination of treatment to assess the efficacy of the therapy. Eradication rate was calculated by intention-to-treat and per-protocol analysis. Results: Two hundred seventy-nine patients (123 male, 156 female) were eligible for randomization. In per-protocol analysis (n=247), Helicobacter pylori was eradicated with ranitidine bismuth citrate- and lansoprazole-based regimens in 74,6% and 69,2% of cases, respectively (p>0,05). Intention-to-treat analysis (n=279) revealed that eradication rates were 65,1% and 63,6% in ranitidine bismuth citrate- and in lansoprazole-based regimens, respectively (p>0,05). Both regimes were well-tolerated, and no serious adverse event was observed during the study. Conclusion: Ranitidine bismuth citrate-based regimen is at least as effective and tolerable as the classical proton-pump inhibitor-based regimen, but none of the therapies could achieve the recommendable eradication rate.
Keywords: Ranitidine bismuth citrate; lansoprazole; Helicobacter pylori; eradication; DUODENAL-ULCER; 2 ANTIBIOTICS; CLARITHROMYCIN; INFECTION; AMOXICILLIN; OMEPRAZOLE; MANAGEMENT; RESISTANCE; RECURRENCE; BLIND